Metabolic Disorders in Patients with Chronic Hepatitis B Virus Infection: Coffee as a Panacea? (ANRS CO22 Hepather Cohort) - Tangui Barré; Hélène Fontaine; Stanislas Pol; Clémence Ramier; Vincent Di Beo; Camelia Protopopescu; Fabienne Marcellin; Morgane Bureau; Marc Bourlière; Céline Dorival; Ventzislava Petrov-Sanchez; Tarik Asselah; et al. (Antioxidants, 2022)
People living with chronic hepatitis B virus (HBV) infection are at high risk of liver disease progression, which is positively associated with metabolic disorders, but inversely associated with dyslipidemia. Diet, including dietary antioxidants, is a lever of metabolic disorder management. In particular, elevated coffee consumption is associated with different metabolic outcomes in the general population. We aimed to test whether such associations occur in HBV-infected people. Based on cross-sectional data from the ANRS CO22 Hepather cohort, we performed logistic regression models with (i) dyslipidemia, (ii) hypertension, and (iii) diabetes as outcomes, and with demographic, clinical, and socio-behavioral (including coffee consumption) data as explanatory variables. Among 4746 HBV-infected patients, drinking ≥3 cups of coffee per day was associated with a higher risk of dyslipidemia (adjusted odds ratio [95% confidence interval] 1.49 [1.10–2.00], p = 0.009) and a lower risk of hypertension (0.64 [0.50–0.82], p = 0.001). It was not associated with diabetes. Elevated coffee consumption was associated with a higher risk of dyslipidemia and a lower risk of hypertension in HBV-infected patients, two effects expected to be associated with favorable clinical outcomes. Further studies should test whether such metabolic benefits translate into reduced mortality risk in this population.